2017
DOI: 10.5603/kp.a2017.0098
|View full text |Cite
|
Sign up to set email alerts
|

Cath lab costs in patients undergoing percutaneous coronary angioplasty — detailed analysis of consecutive procedures

Abstract: Cath lab costs were higher in STEMI patients compared to other groups. In STEMI/NSTEMI they were lower in older patients. In all analysed groups costs were related to the level of procedural difficulty. In female patients, the costs of PCI performed via radial approach were higher compared to femoral approach. Despite younger age, male patients underwent more expensive procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…According to various data, they cost the European economy 160 bn to 210 bn EUR a year (Paczkowska et al, 2014). Due to the importance of this problem, there are a number of papers discussing the cost of CVD in different European countries available (Dziki et al, 2017). These studies used both a top-down and a bottom-up approach to assess the resources used.…”
Section: Discussionmentioning
confidence: 99%
“…According to various data, they cost the European economy 160 bn to 210 bn EUR a year (Paczkowska et al, 2014). Due to the importance of this problem, there are a number of papers discussing the cost of CVD in different European countries available (Dziki et al, 2017). These studies used both a top-down and a bottom-up approach to assess the resources used.…”
Section: Discussionmentioning
confidence: 99%
“…Data presented in these studies again demonstrate reduced rates of complications as the primary driver rather than procedural cost differences. For example, in a small trial, Dziki et al [62] demonstrated comparable procedural cath lab costs when comparing TRI to TFI. Finally, it is noteworthy that the recent, large study [61] from England again demonstrated that the TRI costs are even lower in STEMI patients (348£) as compared to stable CAD patients (153£)-a finding that is concordant with the Safley et al [54] and Amin et al [55] studies from the US implying that the cost savings tend to be higher in high-risk patients.…”
Section: Corroborating Evidence From Around the Worldmentioning
confidence: 99%
“…Thoroughly designed prospective, randomized trial focusing on following issues: multicentricity, pharmacologic approach, thrombus removal and cost-effectiveness analysis would provide the best answer to the aforementioned doubts. Multicentricity is important for significant variability in costs reported for interventional procedures reported by different cath labs [30]. The suggested pharmacologic approach should comprise unfractionated heparin, double bolus of eptifibatide and ticagrelor.…”
Section: Future Perspectivementioning
confidence: 99%